Question Making Training with LOTS, MOTS, and HOTS Cognitive Levels for High School Teachers - Pisriwati, Siti Atwano; Siswanto, Deny Hadi; Hardi, Yuwono; Alghiffari, Eka Kevin (Journal of Social and Community Development, 2024)
The current focus among educators is on assessments that promote higher-order thinking skills, enabling students to develop critical, analytical, and systematic thinking, especially in problem-solving, communication, and collaboration. Nonetheless, some teachers still struggle to create questions that effectively target these skills. This service initiative aims to educate 18 instructors from Muhammadiyah Mlati High School on crafting questions that address advanced cognitive abilities. Using a variety of methods, including lectures, interactive Q&A sessions, group discussions, and presentations, the results indicate that the training participants have successfully grasped the basic principles of designing questions for Higher Order Thinking Skills (HOTS) in education. After participating in four sessions, they have shown competence in categorizing and structuring questions that span Lower Order Thinking Skills (LOTS), Medium Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS).